“Let every soul be subject”: Northern evangelical understandings of submission to civil authority, 1763–1863 - Clark, Robert J. (Kansas State University, 2017)
Evangelical Christians represented a growing and influential subset of American Protestantism in the northern colonies of British America at the time of the War for Independence. Almost a century later, when southern states chose to secede from the Union, evangelical Christianity embodied the most vital expression of American religion, having been widely spread across the nation by decades of revivals. Central to their faith was a commitment to the authority of the Bible in every area of life, including political life. The New Testament seemed to command Christians to obey civil authorities. So, why did northern evangelicals overwhelmingly support the rebellion against English rule, but later criticize southern Christians for rebelling against the Union? Or why, on the other hand, were both of these actions not equally rebellious against civil authority? This dissertation argues that northern evangelical Christians employed Romans 13:1-7 between 1763 and 1863 as a political text either to resist or to promote submission to civil authority in pursuit of an America whose greatness as a democratic republic would be defined primarily by its religious character as an evangelical Protestant Christian nation. The chronological scope of this project spans the century between the end of French and Indian or Seven Years War (1763)—a crucial turning point in Colonial America’s sense of identity in relation to Great Britain—and President Abraham Lincoln’s Emancipation Proclamation (1863)—a crucial turning point in America’s sense of identity over the issue of slavery. Thus, the work explores the debate over American identity during the late-eighteenth and nineteenth centuries from a prominent religious perspective in light of changing understandings of the concept of submission to civil authority. The author views Romans 13:1-7 as a pivotal New Testament text informing evangelical Christian political theory in America between the Revolutionary and Civil Wars. Convictions forged by northern evangelicals in the colonial era regarding America’s status as “chosen” by God, and their attempts to construct a Christian democratic republic on this basis in the nineteenth century drove conscientious adherents of biblical authority to debate and periodically reassess the meaning of these verses in the American context. In this way, evangelicals contributed to the development of a concept that historians would later call “American exceptionalism.” Northern evangelicals, in particular, hoped to define America’s uniqueness by the degree to which those in civil authority reflected and reinforced Protestant Christian values and wedded these to American democratic republican identity. So long as the United States government fostered the attainment of their religious ideal for the nation, northern evangelicals promoted virtually absolute submission to civil authority on the basis of the command, “Let every soul be subject unto the higher powers,” found in Romans 13:1. But when they perceived the state to threaten their goal of a national Christian identity, highly qualified explanations of Romans 13:1 prevailed in northern evangelical pulpits and publications.
Keywords: Romans 13; Evangelical; Civil authority; Submission; Higher powers; Religion and politics